MC‐PEPTITA: A Monte Carlo model for Photon, Electron and Positron Tracking In Terrestrial Atmosphere—Application for a terrestrial gamma ray flash. Issue 5 (22nd May 2015) - Sarria, D.; Blelly, P.‐L.; Forme, F.
Abstract Terrestrial gamma ray flashes are natural bursts of X and gamma rays, correlated to thunderstorms, that are likely to be produced at an altitude of about 10 to 20 km. After the emission, the flux of gamma rays is filtered and altered by the atmosphere and a small part of it may be detected by a satellite on low Earth orbit (RHESSI or Fermi, for example). Thus, only a residual part of the initial burst can be measured and most of the flux is made of scattered primary photons and of secondary emitted electrons, positrons, and photons. Trying to get information on the initial flux from the measurement is a very complex inverse problem, which can only be tackled by the use of a numerical model solving the transport of these high‐energy particles. For this purpose, we developed a numerical Monte Carlo model which solves the transport in the atmosphere of both relativistic electrons/positrons and X/gamma rays. It makes it possible to track the photons, electrons, and positrons in the whole Earth environment (considering the atmosphere and the magnetic field) to get information on what affects the transport of the particles from the source region to the altitude of the satellite. We first present the MC‐PEPTITA model, and then we validate it by comparison with a benchmark GEANT4 simulation with similar settings. Then, we show the results of a simulation close to Fermi event number 091214 in order to discuss some important properties of the photons and electrons/positrons that are reaching satellite altitude.